(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This research paper investigates the relevance of the National Commission for Colleges of Education (NCCE) curriculum in teaching pre-service students the syntactic structure of Arabic sentences. The study aims to assess the effectiveness of the current curriculum in developing students’ understanding and proficiency in Arabic syntax. Through a mixed-methods approach, including surveys, classroom observations, and student assessments, data is collected to evaluate the alignment between the curriculum and students’ learning outcomes. The findings reveal both strengths and areas for improvement in the NCCE curriculum’s coverage of Arabic sentence syntax. The study concludes with recommendations for curriculum enhancements and instructional strategies to better support pre-service students’ acquisition of syntactic skills in Arabic language learning.